Nurses' Perceptions of Caring for Childbearing Women who Misuse Opioids. Issue 1 (January 2016) - Shaw, Michele Rose; Lederhos, Crystal; Haberman, Mel; Howell, Donelle; Fleming, Susan; Roll, John
Abstract: Purpose: This study explored obstetric nurses' perceptions of providing inpatient care during labor, birth, and postpartum to pregnant and parenting women with histories of misusing opioids. Specific aims included to 1) describe common themes associated with nurses' perceptions of caring for this population, and 2) identify specific areas for intervention development. Study Design and Methods: Grounded theory methods, as described by Corbin and Strauss, were used to guide data collection and to identify common themes. Initially, eight inpatient obstetric nurses working in large, urban birthing centers in Washington State were interviewed using semistructured interviews. Follow-up interviews with four of the nurses were conducted to validate emergent themes. Results: Four themes were derived: needing more knowledge, feeling challenged, expressing concern for mother and infant, and knowing the truth. Clinical Implications: The four themes can have an impact on nursing practice and patient outcomes by providing specific areas for intervention development focusing on this population of vulnerable women. Nurses described several ideas for intervention development including continuing education offerings relevant to caring for mothers who misuse opioids, collaborating with providers to design education, reevaluating pain-management philosophies and practices at all levels, and working with social workers to explore available and needed community resources. Future research includes the evaluation of newly developed personalized interventions; the examination of the empirical linkages among key mother and child health outcomes; the delivery of specific nursing therapeutics; and the exploration of providers' and patients' perceptions and knowledge of opioid misuse during pregnancy, birth, and beyond. Abstract : Misuse of prescription and illicit opioids among women of childbearing age has dramatically increased over the last 30 years in the United States. This study explores nurses' perceptions of challenges and opportunities in providing nursing care for childbearing women who misuse opioids and their babies who have been exposed to opioids during pregnancy.